2009
DOI: 10.1080/13813450902835690
|View full text |Cite
|
Sign up to set email alerts
|

Growth effects of insulin and insulin analogues

Abstract: The definition of mitogenic activity of insulin is controversial. Under physiological conditions, mitogenic refers to cell proliferation and tissue repair. In pathological conditions, it may refer to stimulation of tumour cells in pre-existing (undiagnosed) tumours. The in vitro investigations using benign and malignant cell lines compare proliferative activity of insulin molecules (animal, human and analogues). In these studies, inclusion of [B10-Asp] insulin would be a valuable link to the existing evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 85 publications
1
30
0
Order By: Relevance
“…The MAPK and PI3K pathways are canonical signaling pathways downstream of IR and IGF1R activation [6]. Ovarian organoids cultured with inhibitors of the insulin/IGF pathway appeared to have more MIS expression in the granulosa cells indicating that the ovary has endogenous production of IGF that in ex vivo 3D culture is detrimental to the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPK and PI3K pathways are canonical signaling pathways downstream of IR and IGF1R activation [6]. Ovarian organoids cultured with inhibitors of the insulin/IGF pathway appeared to have more MIS expression in the granulosa cells indicating that the ovary has endogenous production of IGF that in ex vivo 3D culture is detrimental to the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of IR or IGF1R by ligand binding activates downstream signaling pathways including the phosphatidylinositiol 3-kinase (PI3K) and mitogen-activated protein kinase (MAPK) pathways. In turn, proliferative and anti-apoptotic pathways are activated, including Akt, glycogen synthase kinase 3 β (GSK3β), Bcl2, and Bad [6]. …”
Section: Introductionmentioning
confidence: 99%
“…There are several uncertainties which make it very difficult to answer the question decisively (Hansen 2008). There seems to be a consensus that insulin and insulin analogues have growth-promoting activity (Sandow 2009). Moreover, insulin and insulin analogues have no carcinogenic activity (cell transformation) and are not a co-carcinogen when evaluated in special toxicology (Sandow 2009).…”
Section: In Vitro/ex Vivo Cell Culture Systemsmentioning
confidence: 99%
“…There seems to be a consensus that insulin and insulin analogues have growth-promoting activity (Sandow 2009). Moreover, insulin and insulin analogues have no carcinogenic activity (cell transformation) and are not a co-carcinogen when evaluated in special toxicology (Sandow 2009). Although Giorgino et al (1991) found that supraphysiological overexpression of IRs does favour ligand-dependent cell transformation in vitro, which underlines the potency of insulin to do so, it certainly does not mean that this occurs in vivo.…”
Section: In Vitro/ex Vivo Cell Culture Systemsmentioning
confidence: 99%
“…It is, however, difficult to predict results in vivo on the basis of in vitro data [23], and in vitro studies do not conclusively support IGFR activation as the mechanism of increased mitogenic activity. The mitogenic action of insulin glargine is increased in certain cell lines with high IGFR:IR ratios [6, 7, 2428], but other cell lines with high IGFR:IR ratios do not respond to insulin glargine treatment with increased proliferation [4, 5, 7, 24, 25, 2934].…”
Section: Discussionmentioning
confidence: 99%